Enhancing me : the hope and the hype of human enhancement - Moore, Pete, 1962- (TechKnow., 2008)
Science is developing more and more potential for human beings to enhance themselves. The pace of change is rapid, and some people are already warning that we are heading for a post-human future populated by ever-lasting, self-sustaining intelligence systems into which the contents of a human mind have been poured ... Is this true? In Enhancing Me, Pete Moore examines the ways in which technology can change our bodies, our brains, our emotions, and how long we live. He talks to people who have actually been 'enhanced' to find out what it's like and how beneficial it is; and to the experts to fi.